Analysis of circulating miRNAs in patients with familial hypercholesterolaemia treated by LDL/Lp(a) apheresis - Dlouha, Dana; Blaha, Milan; Blaha, Vladimir; Fatorova, Ilona; Hubacek, Jaroslav A; Stavek, Petr; Lanska, Vera; Parikova, Alena; Pitha, Jan (Atherosclerosis. Supplements, 2017)
BACKGROUND: LDL/Lp(a) apheresis therapy is a well-established method of aggressively lowering LDL and Lp(a). Recently, miRNAs have been discussed as markers of vascular status including atherosclerosis. MiRNAs inhibit post-transcriptional processes through RNA duplex formation resulting in gene silencing or regulation of gene expression. MATERIALS AND METHODS: We measured a profile of 175 plasma-circulating miRNAs using pre-defined Serum/Plasma Focus Human microRNA PCR Panels in pooled samples of 11 subjects with familial hypercholesterolaemia under long-term apheresis treatment. Subsequently we analysed expressions of ten pre-selected miRNAs potentially involved in lipid homeostasis in the same group of subjects. We compared plasma-circulating miRNA levels isolated from peripheral blood collected immediately before and after apheresis. RESULTS: The greatest differences in plasma levels were found in miR-451a, miR-16, miR-19a/b, miR-223 and miR-185. In subsequent individual miRNA assay we detected a significant increase in miR-33b levels after apheresis (P < 0.05). Additionally, correlations between plasma lipids and miR-33a (P < 0.04) and miR-122 (P < 0.01) have been determined. Moreover, miR-122 levels in LDLR homozygotes were higher compared to heterozygotes after, but not before, apheresis treatment (P < 0.04). CONCLUSIONS: LDL/Lp(a) apheresis has an impact on miRNAs associated with lipid homeostasis and vascular status.
Keywords: senioři; Cholesterol, LDL; Genetic Predisposition to Disease; hyperlipoproteinemie typ II; Homozygote; Heterozygote; Time Factors; transkriptom; výsledek terapie; Middle Aged; mužské pohlaví; Blood Component Removal; Adult; fenotyp; Transcriptome; miRNA; Phenotype; ženské pohlaví; Humans; separace krevních složek; cirkulující mikroRNA; lipoprotein (a); biologické markery; Hyperlipoproteinemia Type II; časové faktory; Familial hypercholesterolaemia; lidé středního věku; homozygot; Apheresis; Circulating MicroRNA; LDL-cholesterol; dospělí; Biomarkers; genetická predispozice k nemoci; Female; Aged; Treatment Outcome; lidé; Male; Lipoprotein(a); heterozygot